Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Konsumen (Studi Pada Pengguna Sepeda Motor Merek Yamaha Dari Kalangan Mahasiswa Universitas Diponegoro Semarang) - Beladin, Muhammad Igor; Dwiyanto, Bambang Munas (Diponegoro Journal of Management, 2013)
This study aims to determine how much influence of product quality, service quality, and brand image to consumer satisfaction to provide solutions problems experienced by Yamaha motorcycle of decreased level in sales, market share, and user dissatisfaction on 2012 in Indonesia. The population used in this study is the students in Diponegoro University Semarang who use Yamaha motorcycle. Samples in this study were 100 respondents and the techniques used are non-probability sampling technique with Accidental Sampling approach. The researcher use validity test, reliability test, linier regression analysis, and hypothesis test supported by SPSS Statistics computer program version 17.0. Independent variables are product quality, service quality, brand image and dependent variable is consumer satisfaction. The result of research showed that product quality, service quality, and brand image Â have positive and significant impact on consumer satisfaction. The results of analysis using the coefficient of determination is 54,5%Â  consumer satisfaction can be explained by variations of the product quality, service quality, brand image, while 45,5% explained by other variables that are not included in this study.